2013
DOI: 10.1007/s10735-013-9507-6
|View full text |Cite
|
Sign up to set email alerts
|

Expression and redistribution of β-catenin in the cardiac myocytes of left ventricle of spontaneously hypertensive rat

Abstract: Beta-catenin is not only an adhering junction protein, but also the central player of the canonical Wnt signalling pathway. In order to investigate the roles of β-catenin in the mechanism of myocardial hypertrophy, we determined the expression and distribution of β-catenin in the cardiomyocytes of spontaneously hypertensive heart failure (SHHF) rats and age-matched Wistar-Kyoto (WKY) rats. We identified the reducing of β-catenin expression in the membrane protein fraction but increasing in the nuclear protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 26 publications
5
26
0
1
Order By: Relevance
“…A study by Zheng et al [26] implicated β-catenin in the pathophysiology of hypertension, which is the main risk factor of LVH in clinical settings [2]. Clinical and experimental studies have shown that the renin-ANG-aldosterone system (RAAS) is over-activated in cardiac hypertrophy and heart failure [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Zheng et al [26] implicated β-catenin in the pathophysiology of hypertension, which is the main risk factor of LVH in clinical settings [2]. Clinical and experimental studies have shown that the renin-ANG-aldosterone system (RAAS) is over-activated in cardiac hypertrophy and heart failure [31].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, conditional deletion of the β-catenin gene significantly reduced the hypertrophic responses of animals [12]. Furthermore, Zheng and colleagues [26] reported the nuclear localization of β-catenin in ventricles of hypertensive rats. Aspirin reportedly inhibits Wnt/β-catenin signaling in cancer cells [9], and β-catenin expression can be activated by ANG II exposure [27].…”
Section: Aspirin Downregulates Wnt/β-catenin Signalingmentioning
confidence: 99%
“…Beta-catenin signaling is activated during pathological cardiac remodeling induced by pressure overload in injured arteries and after myocardial infarction [14]. In addition, it was found to induce apoptosis in other mammalian cell types [16][17][18], heart failure in rats [19] and cardiac fibrosis [20]. However, the role of b-catenin in apoptosis, fibrosis and survival in cardiomyocytes requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…1A). In previous studies, the authors observed cardiac fibrosis and apoptosis in a diabetic animal model [19,31]. In addition, b-catenin protein expression in diseased animal models was determined.…”
Section: Expression Patterns Of B-catenin In Human Infarct Hearts Andmentioning
confidence: 99%
See 1 more Smart Citation